Apply crytography to achieve optimality in a game-theoretic problem - Reza, Adnan; Mahmud, Akib; Sabrin, Shaila (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.